Les noirs à l’heure de l’indépendance jamaïcaine : histoire d’une majorité marginale - Antony Ceyrat (Études Caribéennes)
The article deals with the status of a Black identity in Jamaica when it became independent from the United Kingdom in 1962. Dominated by the Euro-Creoles, pauperized and facing an inadequate political offer, the African population suffers from the lack of an institutionalized blackness, melted into “Creole multiracialism”. This study highlights the importance of history and memory issues in the process of building up social identities, and underlines the central role of culture in conflicts of power.